UPAYA MENINGKATKAN PARTISIPASI BAPAK-BAPAK DALAM DOA BERSAMA MELALUI PENDEKATAN KATEKESE DI KBG BUNDA PENGHIBUR ORANG BERDUKA CITA WERI - Agustina Somi Juan; Alodia Donata Olivia Aran; Emanuel Nunggu (JOURNAL OF COMMUNITY DEDICATION, 2026)
Participation in church life, especially in communal prayer activities at the Basic Ecclesial Community (KBG) level, is an important aspect of strengthening faith. However, in reality, not all members actively participate, particularly adult men. This situation is also found in KBG Bunda Penghibur Orang Berduka Cita Weri, where the attendance of men in communal prayer activities is still relatively low.  This study aims to understand the factors behind the low participation of men and to examine how a catechetical approach can help improve their involvement. The research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the low participation of men is influenced by work commitments, fatigue, and a lack of interest in activities that are perceived as too rigid. Through a more relaxed, dialogical, and life-oriented catechetical approach, men begin to feel more comfortable and gradually show increased involvement. Therefore, a contextual and participatory catechetical approach can be an effective way to enhance the participation of community members, especially men, in communal prayer activities at the KBG level.